(untitled) (Quinto Sol, 2013)
Scientific knowledge about La Pampa province prehispanic past was in second plan of relevance until a few years ago. Nowadays, once this situation was reverted, we have at our disposal a wide panorama about its prehistory, from the earliest peuplement to the coexistence of indigenous peoples with hispanic society. Such knowledge was achieved due to the efforts of several archaeologists and students, but especifically to the pioneer research work of Carlos Gradin. This paper deals with the latest advances in archaeological research of the center-south of La Pampa. In addition to academic research, new approaches in archaeology require the development of participative tasks with local communities in order to make decisions about the final destiny of research results and of the material evidences that make up a part of the cultural local heritage.